Exposure to source-specific air pollution and risk for type 2 diabetes: a nationwide study covering Denmark. (14th March 2022) - Sørensen, Mette; Poulsen, Aslak H; Hvidtfeldt, Ulla A; Frohn, Lise M; Ketzel, Matthias; Christensen, Jesper H; Brandt, Jørgen; Geels, Camilla; Raaschou-Nielsen, Ole
Abstract: Background: Only few epidemiological studies have investigated whether chronic exposure to air pollution from different sources have different impacts on risk of diabetes. We aimed to investigate associations between air pollution from traffic versus non-traffic sources and risk of type 2 diabetes in the Danish population. Methods: We estimated long-term exposure to traffic and non-traffic contributions of particulate matter with a diameter <2.5 µg (PM2.5 ), elemental carbon (EC), ultrafine particles (UFP) and nitrogen dioxide (NO2 ) for all persons living in Denmark for the period 2005–17. In total, 2.6 million persons aged >35 years were included, of whom 148 020 developed type 2 diabetes during follow-up. We applied Cox proportional hazards models for analyses, using 5-year time-weighted running means of air pollution and adjustment for individual- and area-level demographic and socioeconomic covariates. Results: We found that 5-year exposure to all particle measures (PM2.5, UFP and EC) and NO2 were associated with higher type 2 diabetes risk. We observed that for UFP, EC and potentially PM2.5, the pollution originating from traffic was associated with higher risks than the non-traffic contributions, whereas for NO2 similar hazard ratios (HR) were observed. For example, in two-source models, hazard ratios (HRs) per interquartile change in traffic UFP, EC and PM2.5 were 1.025, 1.045 and 1.036, respectively, whereas for non-traffic UFP, EC and PM2.5, the HRs were 1.013, 1.018 and 1.001, respectively. Conclusions: Our finding of stronger associations with particulate matter from traffic compared with non-traffic sources implies that prevention strategies should focus on limiting traffic-related particulate matter air pollution.